FACTORS AFFECTING THE FINANCIAL SUSTAINABILITY OF INSURANCE COMPANIES AND THEIR MANAGEMENT (World Economics and Finance Bulletin, 2022)
This article examines the factors influencing the financial stability of insurance companies and the processes of their management. It should be noted that one of the main external factors influencing the financial stability of insurance companies is the analysis of the legal framework for regulating this system in the country. In addition, the specific features of each of the external and internal factors affecting the financial stability of insurance companies in terms of their impact on the financial condition of the company are studied
Keywords: Insurance Companies; Financial Stability; Factors Affecting Financial Stability; External And Internal Factors